HISTORY OF KUNJALI MARAKKARS IN KERALA (International Journal of Food and Nutritional Sciences, 2022)
The Marakkar family traveled to Cochin for trade from Konkan. Their ancestry is not supported by any evidence. According to tradition, they were descended from Arab Muslim traders who arrived in Cochin in the seventh century A.D. to trade with Malabar. Their task was to import rice from Kanara. The local Muslim communities' trading rights were endangered when Cochin Raja made friends with the Portuguese. Their leader, Ismail Marakkar, had been covertly assisting the Zamorin; during the fight between Cochin and Calicut, Marakkar's ships and warehouses were destroyed. They fled Cochin and made their home in Ponnani after becoming concerned about the Portuguese's perceived danger. Portuguese armies and ships assaulted Ponnani between 1507 and 1524, destroying both. The author of this paper, Kunjali Marakkars, is acknowledged.